Quantum Mechanism of Music in theory and Practice (Global Journal of Science Frontier Research, 2020)
Music is such a vast and infinite subject specifically, from the research point of view, it is an endless journey to know where it originates and where it is destined to. Music as time and again has been defined as source of entertainment through playing of some particular instruments. Singing and dancing is considered as standard definition of music this has been taken as 1st part of this research that discusses music in a new perspective, the practical or performing art has been named as Chemistry of Music like different arrangement of chords in a different way creates different effective sounds or Music with musical composition and musical instruments. Secondly, science behind the music has been discussed thoroughly as it is assumed that the sound with its medium not only communicates with a melodious tone but also brings forth some information that in actual way makes a person feel ectasias on receiving that information this is a collaboration between music and science and herein has been named as Physics of Music. And finally the 3rd one is Clinical part, how it interacts with matter whether living or non-living with different formulas and methods. This belongs to music therapists and music healers. It discusses overall effects with all states of matter whether solid, liquid or gases and finally acquires a title Quantum Mechanism of Music in theory and Practice. Hope this will open up a new window for researchers.